Afri Yudha Sistem Informasi Pemesanan Handphone dan Aksesoris Berbasis Web di PT. Grand Group Telekomunikasi - Afri Yuda (Fakultas Sains Dan Teknologi Universitas Islam Asyafiiyah, 2025)
This research aims to develop a web-based ordering information system for PT. Grand Group Telekomunikasi. The research methods include observation, interviews, and literature reviews. Observations were conducted directly on-site to understand the previously used manual system. The developed system facilitates online ordering, reduces recording errors, and enhances data processing efficiency. Results indicate that the system successfully improves customer satisfaction and the company's competitiveness in the telecommunications market. With features such as inventory management, ordering, and reporting, the system supports better decision-making and optimal service